Modularisation approaches in Initial Vocational Education : evidence for policy convergence in Europe? - Pilz, Matthias [Verfasser]; Li, Junmin [Verfasser]; Canning, Roy [Verfasser]; Minty, Sarah [Verfasser] (My University, 2018)
"One response to challenges of national vocational training systems has been a move towards greater flexibility within vocational training systems. This article focuses on an investigation of modularisation as a tool for achieving this flexibility. Many European countries have introduced modular forms into their vocational training system. We investigate whether the global trends set out are producing policy convergence in modularisation in differing countries. This study selects seven European countries to make a detailed analysis and entailed an analysis of each country's Initial Vocational Education and Training programmes. The methodology involved both primary and secondary data collection. The findings demonstrate policy convergence that can be attributed to similar challenges at national level. Modularisation in some countries takes a 'radical' form. Other countries have followed a mixed approach. It is clear that no two countries have adopted the same form of modularisation, although some countries have cited common challenges in the modularisation process." (Author's abstract, BIBB-Doku)
Keywords: L 1.1.3 Modulorientierung; I 2.2 Europa; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; Modularisierung; Berufsbildungssystem; Internationaler Vergleich; EU-Staat; England; Finnland; Dänemark; Polen; Österreich; Ungarn; Frankreich